2019
DOI: 10.15294/jejak.v12i2.21660
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Village Fund Management On Regional Development

Abstract: The obstacles faced by the Regional Government both the Village Government and the District Government are the lack of control over the management of funds originating from Village Fund Allocation. So, the purpose of this study is to analyze themanagement funds and the use of village funds on regional development in Katingan Kuala District, Katingan Regency. The type of research used was qualitative and quantitative research and used casual research methods with characteristics of causal relationship problems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…These findings are also consistent with previous studies, concluding that the government ability to build and provide infrastructure was proven to significantly improve the quality of life of the community [12], [19], including the domains of psychological health, physical health, well-being, socio-cultural aspects, and environmental conditions [14], [15], [45]. However, this study does not support the findings of previous studies which concluded that village funds did not have a significant effect on improving village development and the quality of life of the community [15], [21]. Government spending on health, such as the provision of health resources, did not have any effect on increasing the health quality and life the population either [22], [23].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These findings are also consistent with previous studies, concluding that the government ability to build and provide infrastructure was proven to significantly improve the quality of life of the community [12], [19], including the domains of psychological health, physical health, well-being, socio-cultural aspects, and environmental conditions [14], [15], [45]. However, this study does not support the findings of previous studies which concluded that village funds did not have a significant effect on improving village development and the quality of life of the community [15], [21]. Government spending on health, such as the provision of health resources, did not have any effect on increasing the health quality and life the population either [22], [23].…”
Section: Discussioncontrasting
confidence: 78%
“…Other findings showed that the budgetary governance of city governments in terms of the aspects of transparency, collaboration, involvement and partnership, communication, and accountability had a positive correlation with the quality of life of urban communities [19] and the well-being of the community [20]. On the other hand, another study showed that village funds did not have any significant effect on area/village development [21]. Recent studies have also revealed that the provision of basic services through government budgets had a negative effect on the quality of life of the community [15].…”
Section: Introductionmentioning
confidence: 96%
“…A wellplanned, transparent and accountable village fund management system will show that the performance of the village government is good. The results of this study strengthen the results of studies conducted by Kalontong et al (2019) and Sahusilawane (2021), which prove that IT utilization has a positive impact on organizational performance.…”
Section: Evaluating Inner Modelsupporting
confidence: 85%
“…Finally, the exchange rate of farmers did not increase significantly. [8] The results of statistical analysis of research [9] prove that village funds have no effect on regional development in Katingan. In other words, the increase or decrease in village funds will not have an impact on the ups and downs of regional development progress.…”
Section: Discussionmentioning
confidence: 99%